Analisis Pengaruh Faktor Dominan Terhadap Kinerja Kontrak Pelaksanaan Konstruksi Jaringan Transmisi dari Aspek Biaya, Waktu dan Mutu - Wenny Rosdiana; Sutardi Sutardi (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2021)
The construction of 150 SUTT Transmission Line Jatigede Incomer is located in Sumedang Regency, West Java. The problems that exist in this project are: (1.) Procurement of Materials, (2.) Land acquisition, (3.) Design Changes, and (4.) The Covid-19 pandemic. As a result of these problems, the project was delayed and required an extension of 442 days (245% of the initial contract which was only 180 days) and 4.89% additional cost of the initial contract. This research aims to study the efforts in order to improve contract performance from cost, time and quality aspects. The analysis was carried out using the method of fishbone diagram analysis for two conditions, which were the initial conditions and its improvement efforts in terms of cost, time and quality, while the concept of earned value was to determine the dominant factor that caused the increase in costs and time. From the results of the analysis, it can be said that the dominant factor that affects the increase in costs is design changes which is 95% of the total amendment cost and causes an extension time of 73% of the total additional time for contract amendments. The impact of the covid-19 pandemic which resulted in the termination of the project for approximately 120 days was the dominant factor in the contract amendment (approximately 27% of 442 days). Regarding problems related to material procurement, it only causes 1.36% additional cost of the total cost amendment, which caused by transportation costs. Land acquisition carried out in stages does not result in additional time or additional contract costs. The quality of the foundation and tower structure work can be maintained in accordance with the requirements in the contract.